2021
DOI: 10.1111/jnu.12625
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Report Assessment of Nurses’ Risk for Infection After Exposure to Patients With Coronavirus Disease (COVID‐19) in the United Arab Emirates

Abstract: Purpose Nurses have an increased risk for acquiring COVID‐19 infection. This study assessed levels of risk for exposure to COVID‐19 among nurses, and determined those at the greatest risk. Design A cross‐sectional design was used to assess risk for exposure to COVID‐19 in nurses from five randomly selected governmental hospitals in the United Arab Emirates. Participants completed an online survey (including the World Health Organization survey) to assess their risk for exposure to COVID‐19. Descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Self-reported adherence in this study was relatively high (71%), despite the strict definition used (always adherent to all elements of FPE). As in previous studies, adherence to surgical masks (89%) was higher than adherence to eye protection (73%) 3 ; 4 ; 24 . Note that using a similar definition to previous work by Nichol et al 19 would have yielded a higher self-reported adherence rate (95%), which drastically exceeds the 44% found in hospital nurses in their study 19 and is comparable to the very high rate (97%) seen in Canadian hospitals during care for SARS CoV-1 patients by the end of the SARS CoV-1 epidemic 24 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Self-reported adherence in this study was relatively high (71%), despite the strict definition used (always adherent to all elements of FPE). As in previous studies, adherence to surgical masks (89%) was higher than adherence to eye protection (73%) 3 ; 4 ; 24 . Note that using a similar definition to previous work by Nichol et al 19 would have yielded a higher self-reported adherence rate (95%), which drastically exceeds the 44% found in hospital nurses in their study 19 and is comparable to the very high rate (97%) seen in Canadian hospitals during care for SARS CoV-1 patients by the end of the SARS CoV-1 epidemic 24 .…”
Section: Discussionsupporting
confidence: 78%
“…in Hong Kong, Oman and Italy) (Al 2 ; 15 ; 29 , while others have reported lower rates (e.g. hospitals in the UAE (78% mask adherence, 51% eye protection), the US (42-86%) and Ethiopia (35% masks adherence, 15% for eye protection) 3 ; 4 ; 11 ; 21 .…”
Section: Introductionmentioning
confidence: 98%
“…From the front-line experience, during the outbreak of COVID-19, hospitals strengthened intervention measures for the HHC among healthcare providers, including strengthening education, increasing monitoring frequency, posting notices and warning signs, and other measures. 20 , 21 In addition, healthcare providers may have had a higher self-awareness of and ability to perform HH compared with other daily working conditions in during the contingency status of COVID-19. However, it is not known whether HH behavior and compliance among healthcare providers changed and what kind of changes may have taken place after the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…The nurses have an increased risk of exposure because they give personal care to COVID 19 patients. For instance, they extract blood samples or specimens to detect the virus or do any aerosol-generating intervention, together with not adhering correctly to the set guidelines [24].…”
Section: Risk Levelmentioning
confidence: 99%